HYBRID POLICING AS AN ALTERNATIVE MODEL OF POLICING AGAINTS CYBERCRIME IN THE INFORMATION SOCIETY - Widagso, Kisnu; Hariyani, Orisa Shinta (Indonesian Journal of International Law, 2016)
Crime, within this context cybercrime, has become one of emerging features of social change. This condition generally responded with or demands of different models of policing. Current attempts in policing of cybercrime cases, despite of adequate resources in information system and technology, seemingly ignoring specific characteristics of computing environment in information society. Such ignorance resulting in weak formal social control on cybercrime, reflected on increasing number of cybercrime cases and huge numbers of unsolved cases, lack of trust in police forces, including economic and social cost that follows. So that it’s important to formulate a unique model of policing – hybrid policing, a model of policing enhanced with information system and technology, support and collaboration from stakeholders, including victims